2014
DOI: 10.1088/1748-0221/9/01/c01036
|View full text |Cite
|
Sign up to set email alerts
|

Performance of CMOS imager as sensing element for a Real-time Active Pixel Dosimeter for Interventional Radiology procedures

Abstract: Staff members applying Interventional Radiology procedures are exposed to ionizing radiation, which can induce detrimental effects to the human body, and requires an improvement of radiation protection. This paper is focused on the study of the sensor element for a wireless real-time dosimeter to be worn by the medical staff during the interventional radiology procedures, in the framework of the Real-Time Active PIxel Dosimetry (RAPID) INFN project. We characterize a CMOS imager to be used as det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In recent years, complementary metal oxide semiconductor (CMOS) cameras have been used for X/γ-ray detection and classification [11][12][13][14]. This promising direction has advantages of higher penetration rate and lower cost compared to traditional methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, complementary metal oxide semiconductor (CMOS) cameras have been used for X/γ-ray detection and classification [11][12][13][14]. This promising direction has advantages of higher penetration rate and lower cost compared to traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…This promising direction has advantages of higher penetration rate and lower cost compared to traditional methods. Studies have shown that random bright spots are generated in images recorded by CMOS image sensors under irradiation of X/γ rays [11][12][13]. Xu et al studied the potential of CMOS image sensors and found that both the mean pixel value and the cumulative pixel value have a linear relationship with radiation dose rate [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The radiation dosimeters are divided into two groups, in the aspect of reading, including (1) the passive types, comprising measurement results, which is difficult to read directly. Hence, there is a need for initial special processing (Knoll, 2007), including film badge and thermoluminescent dosimeter (TLD) (Magalotti et al, 2014). Medical personnel within the area of interventional radiology (IVR) are at risk of exposure to high doses of scattered radiation emitted from the patient (Fujibuchi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%